2000
DOI: 10.1007/s004410050055
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of gastrin-releasing peptide immunoreactivity in the brain of the collared dove ( Streptopelia decaocto )

Abstract: The distribution of immunoreactivity after applying an antibody against gastrin-releasing peptide (GRP) was studied in the brain of the collared dove (Streptopelia decaocto). In the forebrain GRP-immunoreactive (GRP-ir) cells were found in the hyperstriatum accessorium, medial and lateral parts of the neostriatum, corticoidea dorsolateralis and temporoparieto-occipitalis areas, hippocampus, pre-and parahippocampal areas and prepiriform cortex. In the brainstem, GRP-ir cells were restricted mainly to the substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 49 publications
(64 reference statements)
0
2
0
Order By: Relevance
“…In comparison with these counterstains, immunocytochemistry against various molecules can reveal nuclear boundaries much more precisely. In the avian midbrain, many studies have investigated the distribution of neurotransmitters and related enzymes (serotonin: Challet et al, ; den Boer‐Visser and Dubbeldam, ; neuropeptide Y, vasoactive intestinal polypeptide, substance P: den Boer‐Visser and Dubbeldam, 2002; gastrin‐releasing peptide: Dubbeldam and den Boer‐Visser, ; glutamic acid decarboxylase‐65: Sun et al, 2005; GABA: Domenici et al, ; Veenman et al, ; Veenman and Reiner, ). In our study, we found anti‐GABA Aβ histology to provide a precise demarcation of neuronal structures in the corresponding areas of the midbrain.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with these counterstains, immunocytochemistry against various molecules can reveal nuclear boundaries much more precisely. In the avian midbrain, many studies have investigated the distribution of neurotransmitters and related enzymes (serotonin: Challet et al, ; den Boer‐Visser and Dubbeldam, ; neuropeptide Y, vasoactive intestinal polypeptide, substance P: den Boer‐Visser and Dubbeldam, 2002; gastrin‐releasing peptide: Dubbeldam and den Boer‐Visser, ; glutamic acid decarboxylase‐65: Sun et al, 2005; GABA: Domenici et al, ; Veenman et al, ; Veenman and Reiner, ). In our study, we found anti‐GABA Aβ histology to provide a precise demarcation of neuronal structures in the corresponding areas of the midbrain.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, Vaillant et al (1979) found substantial quantities of BN-like immunoreactivity in turkey brain; Cassone & Moore (1987) reported the existence of BN-like reactivity in the suprachiasmatic region of house sparrow and Berk & Smith (1994) described projection of BN-immunoreactive cells to the vagal complex of the pigeon. More recently, Dubbeldam & den Boer-Visser (2000) studied in detail the distribution of GRP immunoreactivity in the brain of the dove. These investigations suggested that receptors for BN-like peptides, in particular GRP, should exist in the avian brain, and here we provide evidence for GRP-R and BRS-3.5 expressions in the brain.…”
Section: Iwabuchi Et Almentioning
confidence: 99%